Talkin’ About a Revolution. Changes and Continuities in Fruit Use in Southern France From Neolithic to Roman Times Using Archaeobotanical Data (ca. 5,800 BCE – 500 CE) - Bouby, Laurent; Bonhomme, Vincent; Cabanis, Manon; Durand, Frédérique; Figueiral, Isabel; Flottes, Laurie; Marinval, Philippe; Martin, Lucie; Paradis, Laure; Pinaud, Rachël; Ros, Jérôme; Rovira, Núria; et al. (Frontiers in Plant Science, 2022)
The use and socio-environmental importance of fruits dramatically changed after the emergence of arboriculture and fruit domestication in the eastern Mediterranean, between the 5th and the 3rd millennia BCE. Domesticated fruits together with cultivation techniques apparently reached the western Mediterranean via colonial activities during the 1st millennium BCE - early 1st millennium CE. However, the pace and chronology of this diffusion and the recompositions in diversity, to adapt to new socio-environmental conditions, remain poorly known. In this study we investigate archaeobotanical records in Southern France from the Neolithic to the end of the Roman empire (ca. 5800 BCE – 500 CE) to assess changes in fruit use as well as the emergence, spread and evolution of fruit cultivation. We explore changes in native traditions faced with innovations brought by Mediterranean colonization and how domesticated fruit cultivation spread from the Mediterranean to more temperate areas. Archaeobotanical data from 577 assemblages were systematically analysed distinguishing two datasets according to preservation of plant remains (charred vs. uncharred), as this impacts on the quantity and diversity of taxa. The 47 fruit taxa identified were organized in broad categories according to their status and origin: exotic, allochtonous cultivated, indigenous cultivated, wild native. We also analysed diversity, quantity of fruits compared to the total of economic plants and spatio-temporal variations in the composition of fruit assemblages using correspondence factor analyses. Archaeobotanical data reflect variations and continuities in the diversity of species used through time and space. In the Mediterranean area, significant changes related to the arrival of new plants and development of fruit cultivation occurred mainly, first during the Iron Age (6th-5th c. BCE), then in the beginning of the Roman period. Large cities played a major role in this process. In agreement with archaeological information, archaeobotanical data reveal the predominance of viticulture in both periods. However, arboriculture also included other fruit species that have been subject to less intensive and specialized cultivation practices. Most significantly, this study pinpoints the continuous contribution of native, supposedly wild fruits throughout the chronology. Despite the homogenizing Roman influence, results reveal clear differences between the Mediterranean and temperate regions.